A review of recent advances in foam-based fracturing fluid application in unconventional reservoirs - Yekeen, N. (Korean Society of Industrial Engineering Chemistry, 2018)
Foam-based fracturing fluid application in unconventional reservoirs has recently attracted prodigious attention, due to their high apparent viscosity and ultra-low water contents, which enhanced their potential applications as proppants carrier fluids in water sensitive formations. A comprehensive review of existing literature on the applications and recent advancement of foam fracturing fluid is conducted in this study. Results of experimental studies, simulations predictions and field applications were extensively discussed. Challenges and knowledge gaps were identified and directions for future studies were suggested. The review literature suggested that stable foam fracturing fluids can increase the productivity of the fractured wells. Â© 2018 The Korean Society of Industrial and Engineering Chemistry